Hydrologic impacts of lined gravel pits, Colorado Front Range - Rach, Gavin, author; Ronayne, Michael, advisor; Sanford, William, committee member; Bailey, Ryan, committee member (Colorado State University. Libraries, 2018)
Sand and gravel quarries are a major source of natural aggregate. Gravel pits often excavate below the water table and therefore can influence alluvial aquifer groundwater flow directions and groundwater-surface water interaction. By regulation in the state of Colorado, low-permeability liners are installed after extraction to minimize water seepage into the pit. The liner impedes flow and disturbs the local water table, creating mounding on the upgradient side and shadow drawdown on the downgradient side. To better understand the magnitude and extent of these effects, numerical groundwater modeling was conducted for a study area along the Saint Vrain Creek alluvial aquifer in Colorado that contains an active gravel pit. The numerical model was based on a revised conceptual model, including a reinterpretation of the bedrock surface, and was calibrated using measured groundwater levels and estimated groundwater-surface water exchange rates constrained by streamflow gaging data. Two transient modeling scenarios were developed: a base case pre-mining scenario and a post-mining lined-pit scenario. The hydrologic effects of the pit liner were quantified through a detailed comparison of the scenarios. Model results indicate that the liner has a significant effect on water-table elevation in the vicinity of the pit during the non-irrigation season (October-March). In March, upgradient mounding produced by the liner exceeds 0.5 m at an approximate distance of 100 m, whereas the drawdown exceeds 0.3 m at this distance on the downgradient side of the pit. The magnitude of these liner-induced changes is less than other seasonal variability in hydraulic head, particularly the variability associated with irrigated agriculture (seasonally active irrigation ditches). During the irrigation season, simulated hydraulic heads are similar in both model scenarios, demonstrating that irrigation ditches are a major control on groundwater flow. Despite significant water table elevation change in parts of the year, groundwater discharge to the stream increased by 0.11% of the total streamflow at its maximum, demonstrating this particular pit liner has a negligible effect on the Saint Vrain Creek.